Resolving dynamics and function of transient states in single enzyme molecules - Hugo Sanabria (Nature Portfolio, 2020)
T4 Lysozyme (T4L) is a model protein whose structure is extensively studied. Here the authors combine single-molecule and ensemble FRET measurements, FRET-positioning and screening and EPR spectroscopy to study the structural dynamics of T4L and describe its conformational landscape during the catalytic cycle by an extended Michaelis–Menten mechanism and identify an excited conformational state of the enzyme.